CO2 LASER THERAPY IMPROVING THE SEXUAL LIFE OF WOMEN AFTER BREAST CANCER TREATMENT (38 CASES) - Moura, Jackson Roberto de; Moura, Jackline Zonta de; Moura Júnior, Jackson Roberto de; Moura, Jardel Antônio da Silva; Teixeira, Áquilla Henrique Gonçalves (Mastology, 2020)
Objective: To verify the response to CO2 laser therapy in vaginal dryness among women submitted to treatment in a service in the State of Minas Gerais, Brazil. Methods: Descriptive, prospective case series study based on cases that were treated by the same staff from January 2019 to December 2019, storing predefined information and analyzing the data using the software R and SPSS PC. Results: Thirty eight women with mean age of 62.5 years + 9.1 (ranging from 48 to 82 years of age) were treated in the service for vaginal dryness. We observed total improvement of vaginal dryness in 94% of the cases. Improvement in sexual activity was observed in 83% of the cases, and increase in sexual relations, 71%. The satisfaction with the treatment was of 95%. We did not find statistical significance for the use of tamoxifen, anastrozole, previous chemotherapy and interval between surgery and laser therapy (p>0.05). Conclusion: The study shows good results of CO2 laser therapy in the improvement of vaginal dryness and sexual activity; however, the sample is limited for the statistical analysis of subgroups.